2010
DOI: 10.1111/j.1574-695x.2010.00674.x
|View full text |Cite
|
Sign up to set email alerts
|

Aggregatibacter actinomycetemcomitansaccelerates atherosclerosis with an increase in atherogenic factors in spontaneously hyperlipidemic mice

Abstract: Cariogenic and periodontal pathogens are thought to be etiological factors in the development of cardiovascular disease. We assessed the involvement of the periodontal pathogen Aggregatibacter actinomycetemcomitans and cariogenic pathogen Streptococcus mutans in the development of atherosclerosis in apolipoprotein E-deficient spontaneously hyperlipidemic (Apoe(shl)) mice. The mice were treated intravenously with A. actinomycetemcomitans HK1651, S. mutans GS-5, or phosphate-buffered saline three times a week fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
2
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 46 publications
1
58
2
3
Order By: Relevance
“…Our results may initially appear to be contradictory to those published recently by Zhang et al (2010), who, also using the ApoE null mouse model (but no BA), reported that S. mutans did not increase atherosclerotic plaque growth. The results demonstrated that atherosclerotic plaques in infected mice were virtually identical to those in the PBS control mice, whereas our results demonstrated significantly increased plaque size and area in mice with BA and demonstrated a trend toward increased plaque even without BA.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results may initially appear to be contradictory to those published recently by Zhang et al (2010), who, also using the ApoE null mouse model (but no BA), reported that S. mutans did not increase atherosclerotic plaque growth. The results demonstrated that atherosclerotic plaques in infected mice were virtually identical to those in the PBS control mice, whereas our results demonstrated significantly increased plaque size and area in mice with BA and demonstrated a trend toward increased plaque even without BA.…”
Section: Discussioncontrasting
confidence: 99%
“…The results demonstrated that atherosclerotic plaques in infected mice were virtually identical to those in the PBS control mice, whereas our results demonstrated significantly increased plaque size and area in mice with BA and demonstrated a trend toward increased plaque even without BA. Most significantly, Zhang et al (2010) used S. mutans strain GS-5, a strain that we have previously reported cannot invade HCAECs. Thus, the results from Zhang et al (2010) are consistent with and provide additional support for the hypothesis that only invasive S. mutans strains are associated with atherosclerotic pathology.…”
Section: Discussionmentioning
confidence: 99%
“…26,27) Recent observations revealed that A.a. infection upregulated the expression of several chemokines, including MCP-1, CCL19, CCL21, and CCR7, which mediate the recruitment of macrophages. 28) Our findings suggest that a specific periodontal pathogen, A.a., plays a pivotal role in the development of ventricular remodeling after MI through enhanced macrophage infiltration. However, the numbers of MCP-1 positive cells were statistically comparable between the two groups.…”
mentioning
confidence: 67%
“…The heart was then carefully dissected and removed. The upper half of the heart, which contains the aortic origin, was separated and embedded in Tissue-Tek(Fisher Scientific, Newark, DE, USA)OCT compound in cryomolds, and frozen sections of the proximal aorta were prepared as described previously (15). …”
Section: Quantification Of Atherosclerotic Lesion Areamentioning
confidence: 99%
“…We have previously shown that Aggregatibacter actinomyctemcomitans(Aa)bacteremia accelerated the progression of atherosclerosis through induction of inflammation and promotion of lipid oxidation in apolipoprotein E (apoE)-deficient spontaneously hyperlipidemic(KOR-Apoe shl )mice (15,16). Periodontal bacteria such as Aa and their components may have direct access to the circulation through bleeding periodontal pockets.…”
Section: Introductionmentioning
confidence: 99%